2013
DOI: 10.1016/j.socscimed.2013.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Misrecognition of need: Women's experiences of and explanations for undergoing cesarean delivery

Abstract: International rates of operative delivery are consistently higher than the World Health Organization determined is appropriate. This suggests that factors other than clinical indications contribute to cesarean section. Data presented here are from interviews with 115 mothers on the postnatal ward of a hospital in Northeast England during February 2006 to March 2009 after the women underwent either unscheduled or scheduled cesarean childbirth. Using thematic content analysis, we found women’s accounts of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 75 publications
4
50
0
1
Order By: Relevance
“…The PRISMA diagram outlines the number of papers included or excluded at each stage of the search process (Figure ). A total of 16 articles are included in this review . The characteristics of each study are summarized in Table , with an in‐depth analysis and critique included in the supplementary material (Appendix S4—available online).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PRISMA diagram outlines the number of papers included or excluded at each stage of the search process (Figure ). A total of 16 articles are included in this review . The characteristics of each study are summarized in Table , with an in‐depth analysis and critique included in the supplementary material (Appendix S4—available online).…”
Section: Resultsmentioning
confidence: 99%
“…The selected studies included women aged between 16 and 43 years old, with the exception of one study where age was not stated . Only two studies reported ethnicity, where the significant majority of women were Caucasian (85% and 97%, respectively) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many women consider childbirth to be a landmark event that colors the rest of their lives (Callister, ; Lobel, ). The majority of American women hope for and prefer vaginal rather than surgical (cesarean) delivery (Pevzner, Preslicka, Bush, & Chan, ; Tully & Ball, ). However, approximately one‐third of all births are surgical deliveries, reflecting a 60% increase since 1996 (Martin, Hamilton, & Ventura et al., ).…”
Section: Mechanisms Of Postcesarean Adjustmentmentioning
confidence: 99%
“…The prevalence of birth by CS is estimated to be 15% worldwide and is more than 20% in developed countries. 12 Because the prevalence of ASD is increasing worldwide, for a variety of reasons, 13,14 it is becoming increasingly important to fully understand any possible longterm effects of birth by CS.…”
mentioning
confidence: 99%